Sodobna cepiva proti vnetju srednjega ušesa - Štrukelj, Borut (Farmacevtski vestnik, 2012)
During the latest decade three conjugate vaccines against infection with Streptococcus pneumoniae were developed by using up-to-date biotechnological methods. The technology is composed of three main steps: isolation of polysaccharide antigenes from the most pathogenic serotypes, expression of recombinant or naive protein carrier and chemically or enzymaticaly driven conjugation. The new technology represents more safe and efficacious bioproduction of vaccines used in infants, adolescents or mature population.
Keywords: cepljenje; konjugirana cepiva; Prevenar; Synflorix; vnetje srednjega ušesa